MEDIA SOSIAL, GAYA HIDUP DAN SERTIFIKASI HALAL TERHADAP MINAT BELI ICE CREAM MIXUE & TEA - Erwin, Sintia; Octavia, Ayu Nurafni (STIE PENA, 2025)
The development of the beverage industry business is currently experiencing very rapid growth. People prefer something that is instant and practical, especially in terms of consuming food and drinks. And the current trend that is popular in society is bubble drinks and ice cream that serve various flavors. One of the ice cream companies in Indonesia is Mixue Ice Cream & Tea. In late 2022 to 2023, there was a decline in interest in buying mixue ice cream products in the city of Semarang. So, it requires a study to increase buying interest which is thought to be influenced by social media variables, lifestyle, halal certification on buying interest in mixue ice cream products in the city of Semarang. This study aims to determine the influence of social media, lifestyle, and halal certification on the interest in buying ice cream mixue & tea products. The population in this study were consumers who bought ice cream mixue & tea products in the Semarang City area with a sample size of 100 respondents. The sampling technique used in this study was the Non-Probability Sampling method with the Purposive Sampling approach. The results of the study showed that in partial testing (t-test) it was found that the variables of social media, lifestyle and halal certification had a positive effect on the purchasing interest variable